Platform Capitalism: Di mana Posisi Ekonomi Syarian dalam Distribusi Risiko Gig Economy? - Musa Andika (At-Ta’awun: Jurnal Mu’amalah dan Hukum Islam, 2026)
The development of the digital economy has given rise to a new business model known as platform capitalism, namely an economic system based on digital platforms that connects service providers and consumers via algorithms. This model drives the growth of the gig economy, but also raises issues regarding the distribution of risk between platforms and workers. In practice, platforms tend to generate profits through transaction fees, whilst workers bear the operational costs, face income uncertainty, and have minimal social protection. This article aims to analyse the inequity in risk distribution within the gig economy and to propose a system based on Islamic economic law as an alternative model for risk distribution. The research employs a qualitative method with a conceptual and legal-normative approach. The research findings indicate that the current platform model is characterised by ‘risk shifting’, namely the transfer of business risks to workers. The principle of Profit and Loss Sharing (PLS) in Islamic economics, through the mudharabah and musyarakah contracts, offers a fairer risk distribution system as profits and losses are shared proportionally between the parties. Consequently, PLS has the potential to serve as a new regulatory framework for building a socially just digital economy.